RETRACTED: Foreign Assistance, Sustainable Development, and Commercial Law: A Comparative Analysis of the Impact of Corruption on Developing Economies - Yu, Ying; Lihong, Huang; Mouneer, Salma; Ali, Hina; Munir, Arshad (Frontiers in Environmental Science, 2022)
The essential purpose of this research is to investigate the relationship between foreign assistance and economic growth. It also analyzes the role corruption might play in influencing this relationship in aid-recipient countries that have similar real gross domestic product (GDP) per capita, but different development patterns. An analysis is performed on specific samples from 2000 to 2019. The model is split into three sections for this purpose: i.e., all developing economies, sub-Saharan Africa (SSA), and the most corrupt countries from regions other than SSA. The difference generalized method of moments (GMM) panel framework is used for empirical analysis. The study concludes that foreign aid does not result in encouraging and significant changes in overall economic growth in developing economies. By contrast, corruption has a powerful impact on foreign aid effectiveness. It is also observed from the analysis that SSA economies receive high levels of foreign assistance, but still cannot extract maximum benefit due to various economic and social problems. Furthermore, foreign assistance effectiveness is almost insignificant in most corrupt economies from other regions.